Black Sunday - Harris, Thomas, 1940- (Signet, 2001)
"Though few would suspect it by looking at him, Michael Lander is the most dangerous man in America. A disgruntled veteran with a fascination for explosives, he pilots television blimps over packed sports stadiums each weekend. When a beautiful terrorist operative hands him the explosive firepower he needs, Lander sets in motion a plan that could turn Super Bowl Sunday into the darkest day in American history."